QUALITY OF MOTOR VEHICLE TAX PAYMENT SERVICE AT SAMSAT SIDOARJO JOINT OFFICE - Muhammad Fajrul Falah; Susi Hardjati (DIA: Jurnal Administrasi Publik, 2022)
This research aims to find out how the Quality of Motor Vehicle Tax Payment Services in the SAMSAT Sidoarjo Joint Office. The method used in research is a qualitative method in which the researcher asks directly to the informant. The data source in this study is from primary data and secondary data. The data collection techniques in this study are: observation, interview, and documentation. This research uses a qualitative approach. The data collection techniques used are: 1) observation, 2) interview, 3) documentation. Based on the results of research on the Quality of Motor Vehicle Tax Payment Services at the SAMSAT Sidoarjo Joint Office, it is quite maximal because of factors that support the successful implementation of regulations and implementation. This can be seen from the aspect of goals, objectives, programs, and policies.